Recurrent Lisch Epithelial Corneal Dystrophy Treated With 5-Fluorouracil: A Case Report and Review of the Literature. Issue 5 (19th May 2023) - Amer, Mona M.; Arze, Karen; Galor, Anat; Sayegh, Yoseph; Dubovy, Sander S.; Karp, Carol L.
Abstract : Purpose: The aim of the study was to describe a case of Lisch epithelial corneal dystrophy (LECD), review its clinical and histopathological features and diagnostic imaging, and introduce a novel treatment approach using topical 5-fluorouracil (5-FU). Methods: A 65-year-old woman presented with a recurrent left-sided corneal lesion consistent with LECD. The lesion was evaluated clinically, with high-resolution optical coherence tomography (HR-OCT), and histologically. The lesion was successfully treated with two 1-week cycles of topical 5-FU. Results: Slit-lamp examination showed an opalescent, whorl-shaped corneal lesion. HR-OCT revealed a trapezoidal area of normal thickness epithelial hyperreflectivity. Histopathology demonstrated a mucosal epithelium with foamy cytoplasm and increased cell size consistent with LECD. Treatment with topical 5-FU resulted in marked clearance of the corneal lesion on slit-lamp examination and HR-OCT. Conclusions: 5-FU may be considered as a treatment option for LECD.